Bumble bee queen pheromones are context-dependent - Margarita Orlova (Nature Portfolio, 2021)
Abstract Queen pheromones have long been studied as a major factor regulating reproductive division of labor in social insects. Hitherto, only a handful of queen pheromones were identified and their effects on workers have mostly been studied in isolation from the social context in which they operate. Our study examined the importance of behavioral and social context for the perception of queen semiochemicals by bumble bee workers. Our results indicate that a mature queen’s cuticular semiochemicals are capable of inhibiting worker reproduction only when accompanied by the queen’s visual presence and the offspring she produces, thus, when presented in realistic context. Queen’s chemistry, queen’s visual presence and presence of offspring all act to regulate worker reproduction, but none of these elements produces an inhibitory effect on its own. Our findings highlight the necessity to reconsider what constitutes a queen pheromone and suggest a new approach to the study of chemical ecology in social insects.